Effect of Vitamin C on Tooth Movement in Terms of Periodontal Ligament Space in Guinea Pigs - Bahirrah, Siti; Nainggolan, Lidya Irani; Pasaribu, Philiph (Dentika: Dental Journal, 2019)
Periodontal ligaments are one of the supporting tissues of teeth that undergo remodeling during the tooth movement process. Vitamin C deficiency inhibits the regeneration of collagen fibers, which are important in tissue remodeling that affects the widening of the periodontal ligament space during the process of tooth movement. The widening of periodontal ligament space can be seen by taking radiographic photos. The purpose of this study was to determine the width of the periodontal ligament space of guinea pigs by administering vitamin C, without vitamin C, and the differences between the two groups. Those samples were grouped into four groups with observation times of 1, 4, 7, and 10 days, and each group consisted of the control group and vitamin C group. Those samples were paired with orthodontic separator rubber. After the specified time was completed, periapical radiographs were taken, and the width of the periodontal ligament space was measured by using Image J software. The mean width of the periodontal ligament space in the vitamin C group was smaller than the control group. Based on this study, it can be concluded that vitamin C has an effect on reducing periodontal ligament space in the process of tooth movement. Key words: periodontal ligament space, vitamin C, tooth movement, remodeling